USP4 function and multifaceted roles in cancer: a possible and potential therapeutic target - Wang, Yizhi (Cancer Cell Int, 2020)
Cancer remains one of the major culprits causing disease-related deaths and leads to a high morbidity and similar mortality. Insidious onset, difficult early detection and a lack of broad-spectrum and effective multi-cancer therapeutic targets have limited the prolongation of cancer patients’ survival for decades. Therefore, a versatile therapeutic target which is involved in various cancer-related signaling pathways and different cancers may be more effective for cancer targeted therapy. USP4, one of the DUBs members which participates in deubiquitination, an inverse process of ubiquitination, can regulate various classical cancer-related signaling pathways, and thereby plays a vital role in some pathological and physiological processes including tumor initiation and progression. Recently, USP4 has been found to exert versatile influences on cells proliferation, migration and invasion, also apoptosis of various tumors. Moreover, USP4 can also act as a prognostic biomarker in several cancers. This review will give a comprehensive introduction of USP4 about its regulatory mechanisms, related signaling pathways, pathophysiological functions and the roles in various cancers which may help us better understand its biological functions and improve future studies to construct suitable USP4-targeted cancer therapy system.